Performances of improved cassava (Manihot esculenta Crantz) cultivars against root rot disease and yield in cassava-maize intercropping systems under natural infection. (1st October 2016) - Awoyemi, Sola Olawale; Afolabi, Clement Gboyega; Popoola, Akinola Rasheed; Odedina, Joy Nwakaego; Adigbo, Sunday Ojo
Abstract: This study examined the performances of 21 cassava cultivars in two cropping seasons on the field against root rot disease and the yield in cassava-maize intercrop. Data were collected on number of root/plant, weight of root (t/ha) and disease severity (DS) on rotted roots at 12 and 16 months after planting (MAP), respectively. There were significant ( P  ≤ 0.05) differences for DS at 12 and 16 MAP in both seasons with cultivar TMS 97/JW2 having the least DS score. TMS 97/JW2 was resistant to the root rot pathogen, while eleven other cultivars were moderately resistant to the disease at 16 MAP. There was no consistency in the roots weight for the cultivars over the two cropping seasons but higher roots weight was recorded at 16 MAP than 12 MAP with different cultivars having highest roots weight at these periods. Intercropping maize with cassava does not have any management potential on root rot development.